Combination effects of flow field structure and assembly force on performance of high temperature proton exchange membrane fuel cells. (3rd January 2021) - Zhang, Tianyu; Li, Jie; Li, Qiang; Yu, Mingfu; Sun, Hong
Summary: In this work, a three‐dimensional, steady state model was developed by combining mechanical equations, Navier‐stokes equation, Maxwell‐Stefan equation, and Butler‐Volmer equation. This model was used to investigate the influences of flow field structure and assembly force on porosity distribution in gas diffusion layer (GDL), species distribution in GDL, and current density distribution in GDL and membrane by extracting uneven porosity in the GDL from mechanical calculation equation to put in mass transfer calculation and electrochemical calculation equation as the known data. The optimum assembly prestress and optimum flow field structure were achieved. The results show combined effect of the assembly force and flow field makes the uneven porosity distribution and remarkable lateral current in the GDL; the channel width/rib width ratio of flow field has significant effects on the performance of the high temperature proton exchange membrane fuel cells (HT‐PEMFC). These results provide the potential to promote the performance and application of HT‐PEMFC. Abstract : A mixture model with mechanical equation was used to mass transfer in PEMFC Flow field and assembly force make uneven porosity distribution in GDL Lateral current in GDL is far more than that in membrane